Altered interferon-γ expression in lymphocytes as a potential peripheral marker of chronic stress-induced cognitive deficit - Palumbo, María Laura (2018)
Fil: Palumbo, María Laura. Universidad Nacional del Noroeste de la Provincia de Buenos Aires. Centro de Investigaciones y Transferencia del Noroeste de la Provincia de Buenos Aires; Argentina